( 1 n ) − ( 1 + 2 1 ) ( 2 n ) + ( 1 + 2 1 + 3 1 ) ( 3 n ) − … + ( − 1 ) n − 1 ( 1 + 2 1 + … + n 1 ) ( n n )
If the value of the expression above equals to S , then what can we conclude?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution bro! reshare it so that others also see ur method.
Log in to reply
This problem recently In our AIITS-3 . Thank god i remembered the answer to this problem ! :)
Thank you :D
Problem Loading...
Note Loading...
Set Loading...
We can write
T r = ( − 1 ) r − 1 ( 1 + 2 1 + 3 1 + . . . . . + r 1 ) ( r n )
⇒ T r = ( − 1 ) r − 1 ∫ 0 1 ( 1 + x + x 2 + x 3 . . . . . + x r − 1 ) ( r n )
⇒ ∑ r = 1 n T r = ∑ r = 1 n ( − 1 ) r − 1 ∫ 0 1 ( 1 + x + x 2 + x 3 . . . . . + x r − 1 ) ( r n )
⇒ ∑ r = 1 n T r = ∫ 0 1 ∑ r = 1 n ( − 1 ) r − 1 ( 1 + x + x 2 + x 3 . . . . . + x r − 1 ) ( r n )
⇒ ∑ r = 1 n T r = ∫ 0 1 ∑ r = 1 n ( − 1 ) r − 1 ( x − 1 x r − 1 ) ( r n )
⇒ ∑ r = 1 n T r = ∫ 0 1 x − 1 1 ∑ r = 1 n ( − 1 ) r − 1 ( x r − 1 ) ( r n )
⇒ ∑ r = 1 n T r = ∫ 0 1 x − 1 1 ∑ r = 1 n ( − 1 ) r − 1 ( x r ) ( r n ) − ( − 1 ) r − 1 ( r n )
⇒ ∑ r = 1 n T r = ∫ 0 1 x − 1 1 ∑ r = 1 n ( − 1 ) r − 1 ( x r ) ( r n ) + ( − 1 ) r ( r n )
⇒ ∑ r = 1 n T r = ∫ 0 1 x − 1 1 ( ∑ r = 1 n ( − 1 ) r − 1 ( x r ) ( r n ) + ∑ r = 1 n ( − 1 ) r ( r n ) )
⇒ ∑ r = 1 n T r = ∫ 0 1 x − 1 1 ∑ r = 1 n ( − 1 ) r − 1 ( x r ) ( r n ) + 0
⇒ ∑ r = 1 n T r = ∫ 0 1 x − 1 1 ∑ r = 1 n ( − 1 ) ( − 1 ) r ( x r ) ( r n )
⇒ ∑ r = 1 n T r = ∫ 0 1 x − 1 1 ∑ r = 1 n ( − 1 ) ( − x ) r ( r n )
⇒ ∑ r = 1 n T r = ∫ 0 1 x − 1 1 ( − 1 ) ( 1 − x ) n
⇒ ∑ r = 1 n T r = ∫ 0 1 1 − x 1 ( 1 − x ) n
⇒ ∑ r = 1 n T r = ∫ 0 1 ( 1 − x ) n − 1
⇒ ∑ r = 1 n T r = n 1
⇒ S = n 1
⇒ S 1 = n
Therefore S 1 is an integer.